PENGARUH PERILAKU KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN JAM TANGAN ALEXANDRE CHRISTIE DI KABUPATEN BUNGO - Lisa Amiyati; Delila Fitri Harahab (Universitas Muara Bungo, 2022)
This study aims to determine the influence of consumer behavior on purchasing decisions Alexandre Cristie watches in Bungo District partially and simultaneously (simultaneously). The method used in this research is a quantitative approach. The sampling technique for this study was accidental sampling with a total population of 96 people and a sample of 96 people. The analytical tool used is multiple linear regression with the results of the study Y = 4.926 + 0.210 ð—1 + 0.092 ð—2 + 0.140 ð—3 + 0.109 ð—4 + e. The partial and simultaneous test results show the influence of consumer behavior variables on purchasing decisions. The R Square value is 0.304 or 30.4%. Where the dependent variable (Y) can be explained by the independent variable of 30.4%, while the remaining 69.6% is influenced by other variables outside the research.